Revisiting head circumference of Brazilian newborns in public and private maternity hospitals - Amorim, Maria do Socorro Teixeira; Melo, Aurea Nogueira de (Arquivos de Neuro-Psiquiatria, 2017)
To revisit the head circumference (HC) of newborns in public and private maternity hospitals; to correlate our findings with the gestational age, gender, and type of delivery; and build and validate graphs and curves.This was a prospective study performed on healthy newborns. Differences in HC were analyzed as a function of gestational age, gender, the healthcare system and the type of delivery. Smoothed percentile curves were created using the least mean squares method.Of the included newborns, 697 were born in private maternity hospitals and 2,150 were born in public maternity hospitals. In all, 839 were born by vaginal delivery, and 1,311 were born by cesarean delivery. At 37 to 42 weeks of gestation, male newborns had a larger HC than females. Infants born in private maternity and those born by cesarean delivery had a larger HC.An important result of the present study is that our analyses allowed us to generate curves and statistically-validated graphs that can be used in clinical neonatal practice.
Keywords: neonatal head circumference; gestational age; gender; public and private maternity; newborn